Organizational behavior - Robbins, Stephen P. (Pearson, 2017)
For undergraduate and graduate courses in Organizational Behavior. Help Students Better Understand Their Behavioral and Interpersonal Skills Long considered the standard for all organizational behavior textbooks, Organizational Behavior provides the research you want, in the language your students understand. This text continues its tradition of making current, relevant research come alive for readers. The 17th Edition has been thoroughly updated to reflect the most recent research and business events within the field of organizational behavior worldwide, while maintaining its hallmark features--clear writing style, cutting-edge content, and intuitive pedagogy. There's a reason why Robbins's textbooks have educated millions of students and have been translated into twenty languages--and it's because of a commitment that provides the kind of engaging, cutting-edge material that helps students understand and connect with organizational behavior.